-3y = x...so we sub in -3y for x in the other equation
-x + 7y = 70
-(-3y) + 7y = 70
3y + 7y = 70
10y = 70
y = 70/10
y = 7
so we sub in 7 for y in either of the original equations to find x
-3y = x
-3(7) = x
-21 = x
so ur solution is (-21,7)
Answer:
D it is d my guy you have fun with that
Answer:
hello
bring the side of the first part of the triangle then you can to bring the (x) of the second traingle
2(x - 3) + 4y - 2(x - y - 3) + 5 =
2x - 6 + 4y - 2x + 2y + 6 + 5 =
6y + 5 <== ur x terms cancel and ur 6's cancel
Answer:
<h2>
(−y−2)(y−3)</h2>
Step-by-step explanation:
I'm just going to factor it for you.
Factor −y^2+y+6
−y^2+y+6
=(−y−2)(y−3)
Answer:
(−y−2)(y−3)